Low-voc environment-friendly titanium-silicon synergistically modified industrial coating and preparation method thereof

CN122917632APending Publication Date: 2026-10-16YANCHENG HUATI CHEM CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611247237.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-17
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

[0006]为了克服现有技术中工业涂层VOC排放较高、钛白粉在树脂体系中分散稳定性较差、涂层耐候性和长期防护性能不足技术问题,本发明的目的在于提供一种低VOC环保型钛硅协同改性工业涂层及其制备方法

Benefits of technology

[0025]This invention employs aluminum sol and γ-glycidyl etheroxypropyltrimethoxysilane to synergistically modify titanium dioxide. The aluminum sol forms a stable inorganic alumina network layer on the titanium dioxide surface, improving its surface stability and weather resistance. The epoxy silane constructs a stable interfacial bonding layer between the titanium dioxide and epoxy resin, enhancing their compatibility and bonding ability. This significantly improves the dispersion uniformity of titanium dioxide in the resin system, reduces agglomeration, and enhances the density and stability of the coating structure. This invention innovatively introduces 2-aminobenzimidazole as a functional synergist. The amino and benzimidazole heterocyclic structures in its molecule can form multiple hydrogen bonds with the epoxy resin system and produce a synergistic interfacial bonding effect with the modified titanium dioxide surface, promoting the formation of a more stable and continuous protective network structure. Compared with conventional corrosion inhibitors, 2-aminobenzimidazole can further improve the integrity of the coating's internal structure and enhance its barrier against moisture, oxygen, and corrosive media penetration, thereby significantly improving the coating's adhesion, corrosion resistance, and long-term service stability. This invention utilizes the synergistic effect of aluminum sol-epoxy silane modified titanium dioxide and 2-aminobenzimidazole to effectively reduce the system's dependence on high-volatility organic solvents while ensuring coating application and mechanical properties. Furthermore, it achieves VOC emission reduction by combining with a low-volatility solvent system. The resulting industrial coating exhibits excellent weather resistance, corrosion resistance, and environmental performance, maintaining good structural stability and protective effects even under complex environments such as ultraviolet radiation, humidity, and salt spray, thus possessing high industrial application value.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122917632A_ABST
    Figure CN122917632A_ABST
Patent Text Reader

Abstract

The application discloses a low-VOC environment-friendly titanium-silicon synergistically modified industrial coating and a preparation method thereof, and belongs to the technical field of industrial coatings. The industrial coating is prepared by taking aluminum sol-epoxy silane synergistically modified titanium dioxide as a functional filler, taking epoxy resin as a film-forming matrix, and cooperating with 2-amino benzimidazole, mica iron oxide, barium sulfate, nano cerium oxide, a curing agent and an organic solvent. The titanium dioxide is synergistically coated and modified by using the aluminum sol and gamma-glycidyl ether oxypropyl trimethoxysilane, an inorganic protective layer and an organic interface coupling layer are constructed on the surface of the titanium dioxide, and the dispersion stability and interface combination capacity of the titanium dioxide are improved. Meanwhile, the compactness and barrier property of the coating structure are enhanced by using the synergistic effect of the 2-amino benzimidazole. The obtained industrial coating has excellent salt mist resistance, weather resistance, adhesion and electrochemical protection performance, can reduce VOC emission, and has good environmental protection performance and long-term protection performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of industrial coating materials technology, specifically to a low-VOC environmentally friendly titanium-silicon synergistic modified industrial coating and its preparation method. Background Technology

[0002] Industrial coatings are widely used in equipment manufacturing, steel structure engineering, rail transportation, petrochemicals, power facilities, and marine engineering, primarily to improve the corrosion resistance, weather resistance, abrasion resistance, and service life of the substrate. With the continuous advancement of national environmental protection policies and the increasing demands for green manufacturing in the industrial sector, traditional high-solvent industrial coatings, due to their high volatile organic compound (VOC) emissions, are gradually becoming unable to meet the needs of environmental regulations and market development. Therefore, developing industrial coatings that combine low VOC emissions, excellent protective performance, and long-term service stability has become an important direction for industry development.

[0003] Titanium dioxide is widely used in industrial coating systems due to its excellent hiding power, weather resistance, and chemical stability. However, ordinary titanium dioxide has high surface activity and is prone to agglomeration in resin systems, resulting in poor dispersion stability and affecting the coating's density, adhesion, and weather resistance. Furthermore, under long-term ultraviolet radiation, humid and hot environments, and corrosive media, the coating is still susceptible to problems such as chalking, loss of gloss, cracking, and decreased protective performance, making it difficult to meet the long-term protection requirements under complex working conditions.

[0004] Existing technologies typically modify titanium dioxide using methods such as inorganic oxide coating and silane coupling agent surface treatment to improve its compatibility and dispersibility in resin systems. However, single modification methods often fail to simultaneously address interfacial bonding, weather resistance, and long-term stability. Furthermore, some industrial coating systems still rely heavily on organic solvents to achieve their application performance, resulting in high VOC emissions and hindering compliance with environmental protection requirements.

[0005] Therefore, developing an industrial coating that combines low VOC emissions, high dispersion stability, excellent weather resistance, and protective properties, and improving the overall performance of the coating through synergistic modification of titanium dioxide and the construction of a stable interface reinforcement system, has significant research value and application prospects. Summary of the Invention

[0006] To overcome the technical problems of high VOC emissions, poor dispersion stability of titanium dioxide in resin systems, and insufficient weather resistance and long-term protective performance of existing industrial coatings, this invention aims to provide a low-VOC, environmentally friendly titanium-silicon synergistic modified industrial coating and its preparation method. This invention uses aluminum sol and γ-glycidyl etheroxypropyltrimethoxysilane to synergistically coat modified titanium dioxide as functional fillers. By constructing a composite structure combining an inorganic alumina network layer and an organosilane interface layer, the interfacial compatibility and dispersion stability between titanium dioxide and the epoxy resin system are improved. Simultaneously, 2-aminobenzimidazole is introduced as a functional synergist, utilizing its special nitrogen-containing heterocyclic structure to enhance the internal forces and interfacial bonding ability of the coating. Combined with mica iron oxide, barium sulfate, nano-cerium oxide, and a low-volatile organic solvent system, an industrial coating with both low VOC emissions and excellent comprehensive performance is prepared. This invention utilizes the synergistic effect of aluminum sol-epoxy silane-modified titanium dioxide and 2-aminobenzimidazole synergistic system to significantly improve the dispersion stability, weather resistance, adhesion and corrosion resistance of the coating while reducing VOC emissions.

[0007] The objective of this invention can be achieved through the following technical solutions:

[0008] A low-VOC, environmentally friendly titanium-silicon synergistic modified industrial coating comprises the following raw materials in parts by weight: 80-150 parts of aluminum sol-epoxy silane synergistic modified titanium dioxide; 60-120 parts of epoxy resin; 0.5-6 parts of 2-aminobenzimidazole; 20-80 parts of mica iron oxide; 20-80 parts of barium sulfate; 1-10 parts of nano-cerium oxide; 25-60 parts of curing agent; and 40-120 parts of organic solvent. The aluminum sol-epoxy silane synergistic modified titanium dioxide is prepared by surface synergistic coating modification of titanium dioxide with aluminum sol and γ-glycidyl etheroxypropyltrimethoxysilane.

[0009] Optionally, the aluminum sol-epoxysilane synergistic modification of titanium dioxide comprises the following raw materials in parts by weight: 100 parts titanium dioxide; 5-25 parts aluminum sol; 3-20 parts γ-glycidyl etheroxypropyltrimethoxysilane; 30-120 parts ethanol; and 40-150 parts deionized water.

[0010] Optionally, the preparation method of aluminum sol-epoxy silane synergistic modification of titanium dioxide includes the following steps:

[0011] (1) Add aluminum sol to a mixed solvent consisting of ethanol and deionized water, stir and mix evenly to obtain an aluminum sol dispersion;

[0012] (2) Add titanium dioxide to the aluminum sol dispersion for dispersion treatment, and then add γ-glycidyl etheroxypropyltrimethoxysilane for surface modification reaction to obtain modified slurry;

[0013] (3) The modified slurry is filtered, washed and dried to obtain aluminum sol-epoxy silane synergistic modified titanium dioxide.

[0014] Optionally, the reaction conditions in step (1) are: stirring at 300-600 rpm for 30-90 min at 25-45°C.

[0015] Optionally, in step (2), the reaction conditions for dispersing titanium dioxide are: at 25-50°C, stirring at 500-1000 rpm for 1-3 hours; and the reaction conditions for surface modification are: at 60-85°C, stirring at 400-800 rpm for 2-6 hours.

[0016] Optionally, the reaction conditions for step (3) are to dry the product at 80–120°C for 6–12 h after filtration.

[0017] Optionally, the curing agent is a mixture of polyamide curing agent and modified alicyclic amine curing agent in a mass ratio of 3 to 4:1; the organic solvent is a mixture of xylene and propylene glycol methyl ether acetate in a mass ratio of 4 to 6:1.

[0018] Optionally, a method for preparing a low-VOC, environmentally friendly titanium-silicon synergistic modified industrial coating includes the following steps:

[0019] S1, aluminum sol-epoxy silane synergistic modification of titanium dioxide, mica iron oxide, barium sulfate and nano cerium oxide are added to a portion of organic solvent for pre-dispersion to obtain a mixed slurry;

[0020] S2, add epoxy resin and 2-aminobenzimidazole to the mixed slurry, and continue to disperse and mix evenly to obtain the coating base material;

[0021] S3, add the remaining organic solvent and curing agent to the coating base material, mix evenly to obtain a high weather-resistant titanium-based anti-corrosion coating composition.

[0022] Optionally, the reaction conditions for step S1 are: dispersion at 800–1500 rpm for 30–90 min at 25–45 °C.

[0023] Optionally, the reaction conditions for step S2 are: stirring at 500-1000 rpm for 1-4 hours at 40-70°C; and the reaction conditions for step S3 are: stirring at 300-800 rpm for 20-60 minutes at 20-40°C.

[0024] The beneficial effects of this invention are:

[0025] This invention employs aluminum sol and γ-glycidyl etheroxypropyltrimethoxysilane to synergistically modify titanium dioxide. The aluminum sol forms a stable inorganic alumina network layer on the titanium dioxide surface, improving its surface stability and weather resistance. The epoxy silane constructs a stable interfacial bonding layer between the titanium dioxide and epoxy resin, enhancing their compatibility and bonding ability. This significantly improves the dispersion uniformity of titanium dioxide in the resin system, reduces agglomeration, and enhances the density and stability of the coating structure. This invention innovatively introduces 2-aminobenzimidazole as a functional synergist. The amino and benzimidazole heterocyclic structures in its molecule can form multiple hydrogen bonds with the epoxy resin system and produce a synergistic interfacial bonding effect with the modified titanium dioxide surface, promoting the formation of a more stable and continuous protective network structure. Compared with conventional corrosion inhibitors, 2-aminobenzimidazole can further improve the integrity of the coating's internal structure and enhance its barrier against moisture, oxygen, and corrosive media penetration, thereby significantly improving the coating's adhesion, corrosion resistance, and long-term service stability. This invention utilizes the synergistic effect of aluminum sol-epoxy silane modified titanium dioxide and 2-aminobenzimidazole to effectively reduce the system's dependence on high-volatility organic solvents while ensuring coating application and mechanical properties. Furthermore, it achieves VOC emission reduction by combining with a low-volatility solvent system. The resulting industrial coating exhibits excellent weather resistance, corrosion resistance, and environmental performance, maintaining good structural stability and protective effects even under complex environments such as ultraviolet radiation, humidity, and salt spray, thus possessing high industrial application value. Attached Figure Description

[0026] The invention will now be further described with reference to the accompanying drawings.

[0027] Figure 1 The infrared spectra of titanium dioxide and titanium dioxide synergistically modified with aluminum sol-epoxy silane are compared. Detailed Implementation

[0028] The present invention will be further described below with reference to specific embodiments. However, the present invention is not limited to the following embodiments. Equivalent adjustments made without departing from the spirit and essence of the present invention should also be considered to fall within the protection scope of the present invention.

[0029] Example 1: The purpose of this example is to verify the effect of aluminum sol-epoxy silane synergistic modification of titanium dioxide and 2-aminobenzimidazole on improving the performance of industrial coatings when the components are used in the lower limit ratio and under lower reaction conditions.

[0030] S1. Add 5 parts of aluminum sol to a mixed solvent consisting of 30 parts of ethanol and 40 parts of deionized water, and stir at 300 rpm for 30 min at 25°C to obtain an aluminum sol dispersion; then add 100 parts of titanium dioxide to the aluminum sol dispersion, and stir at 500 rpm for 1 h at 25°C; then add 3 parts of γ-glycidyl etheroxypropyltrimethoxysilane, and stir at 400 rpm for 2 h at 60°C to obtain a modified slurry; filter and wash the modified slurry, and dry it at 80°C for 6 h to obtain 80 parts of aluminum sol-epoxysilane synergistic modified titanium dioxide;

[0031] S2. Add 80 parts of aluminum sol-epoxy silane synergistic modified titanium dioxide, 20 parts of mica iron oxide, 20 parts of barium sulfate and 1 part of nano-cerium oxide to a mixed solvent consisting of 8 parts of xylene and 2 parts of propylene glycol methyl ether acetate, and disperse at 800 rpm for 30 min at 25°C to obtain a mixed slurry; then add 60 parts of epoxy resin and 0.5 parts of 2-aminobenzimidazole, and stir at 500 rpm for 1 h at 40°C to obtain the coating base material;

[0032] S3. Add 8 parts xylene, 2 parts propylene glycol methyl ether acetate, 18.75 parts polyamide curing agent, and 6.25 parts modified alicyclic amine curing agent to the coating base material, and stir at 300 rpm for 20 min at 20℃ to obtain a low-VOC environmentally friendly titanium-silicon synergistic modified industrial coating.

[0033] Example 2: The purpose of this example is to verify the synergistic effect between aluminum sol-epoxy silane-modified titanium dioxide and 2-aminobenzimidazole when the components are in the median ratio and under appropriate reaction conditions.

[0034] S1. 15 parts of aluminum sol were added to a mixed solvent consisting of 75 parts ethanol and 95 parts deionized water, and stirred at 450 rpm for 60 min at 35°C to obtain an aluminum sol dispersion. Then, 100 parts of titanium dioxide were added to the aluminum sol dispersion, and the mixture was stirred at 750 rpm for 2 h at 40°C. Next, 11.5 parts of γ-glycidyl etheroxypropyltrimethoxysilane were added, and the mixture was stirred at 600 rpm for 4 h at 75°C to obtain a modified slurry. The modified slurry was filtered, washed, and dried at 100°C for 8 h to obtain 115 parts of aluminum sol-epoxysilane synergistic modified titanium dioxide. According to... Figure 1 As shown, the infrared spectrum of unmodified titanium dioxide is mainly characterized by a wavelength of 3435 cm⁻¹. -1 The nearby hydroxyl absorption peak and 560 cm⁻¹ -1 and 450cm -1 The nearby Ti-O lattice vibration peaks indicate that only a small amount of hydroxyl groups and adsorbed water exist on its surface; after synergistic modification with aluminum sol and γ-glycidoxypropyltrimethoxysilane, the peak at 2930 cm⁻¹...-1 2855cm -1 1255cm -1 The appearance of new characteristic absorption peaks at positions such as 1115 cm⁻¹ indicates that the alkyl chains and epoxy groups in the organosilane have been successfully introduced into the surface of titanium dioxide; the Si-O-Si characteristic peak near 1115 cm⁻¹ is significantly enhanced, and the peak at 1040 cm⁻¹ is further enhanced. -1 and 965cm -1 The presence of characteristic absorption peaks for Si-O-Al and Si-O-Ti nearby indicates that a synergistic condensation reaction occurred between the alumina layer formed by the aluminum sol and the silane coupling layer. The above results indicate that aluminum sol-epoxy silane synergistic modification of titanium dioxide has been successfully prepared and a stable inorganic-organic composite interface structure has been formed.

[0035] S2. 115 parts of aluminum sol-epoxy silane synergistic modified titanium dioxide, 50 parts of mica iron oxide, 50 parts of barium sulfate and 5.5 parts of nano-cerium oxide were added to a mixed solvent consisting of 24 parts of xylene and 6 parts of propylene glycol methyl ether acetate. The mixture was dispersed at 1200 rpm for 60 min at 35 °C to obtain a mixed slurry. Subsequently, 90 parts of epoxy resin and 3.25 parts of 2-aminobenzimidazole were added, and the mixture was stirred at 750 rpm for 2.5 h at 55 °C to obtain a coating base material.

[0036] S3. Add 24 parts xylene, 6 parts propylene glycol methyl ether acetate, 31.875 parts polyamide curing agent, and 10.625 parts modified alicyclic amine curing agent to the coating base material, and stir at 500 rpm for 40 min at 30°C to obtain a low-VOC environmentally friendly titanium-silicon synergistic modified industrial coating.

[0037] Example 3: The purpose of this example is to verify the effect of aluminum sol-epoxy silane synergistic modification of titanium dioxide and 2-aminobenzimidazole on the overall performance of industrial coatings when the components are used at the upper limit ratio and under higher reaction conditions.

[0038] S1. 25 parts of aluminum sol were added to a mixed solvent consisting of 120 parts of ethanol and 150 parts of deionized water, and stirred at 600 rpm for 90 min at 45 °C to obtain an aluminum sol dispersion. Then, 100 parts of titanium dioxide were added to the aluminum sol dispersion, and stirred at 1000 rpm for 3 h at 50 °C. Then, 20 parts of γ-glycidyl etheroxypropyltrimethoxysilane were added, and stirred at 800 rpm for 6 h at 85 °C to obtain a modified slurry. The modified slurry was filtered, washed, and dried at 120 °C for 12 h to obtain 150 parts of aluminum sol-epoxysilane synergistic modified titanium dioxide.

[0039] S2. 150 parts of aluminum sol-epoxy silane synergistic modified titanium dioxide, 80 parts of mica iron oxide, 80 parts of barium sulfate and 10 parts of nano-cerium oxide were added to a mixed solvent consisting of 48 parts of xylene and 12 parts of propylene glycol methyl ether acetate. The mixture was dispersed at 1500 rpm for 90 min at 45 °C to obtain a mixed slurry. Subsequently, 120 parts of epoxy resin and 6 parts of 2-aminobenzimidazole were added, and the mixture was stirred at 1000 rpm for 4 h at 70 °C to obtain a coating base material.

[0040] S3. Add 48 parts xylene, 12 parts propylene glycol methyl ether acetate, 45 parts polyamide curing agent, and 15 parts modified alicyclic amine curing agent to the coating base material, and stir at 800 rpm for 60 min at 40℃ to obtain a low-VOC environmentally friendly titanium-silicon synergistic modified industrial coating.

[0041] Comparative Example 1: The purpose of this comparative example is to verify the effect of aluminum sol-modified titanium dioxide on the performance of industrial coatings after replacing aluminum sol-epoxy silane synergistic modification of titanium dioxide.

[0042] S1. Add 15 parts of aluminum sol to a mixed solvent consisting of 75 parts of ethanol and 95 parts of deionized water, and stir at 450 rpm for 60 min at 35°C to obtain an aluminum sol dispersion; then add 100 parts of titanium dioxide to the aluminum sol dispersion, and stir at 750 rpm for 2 h at 40°C; then continue to stir at 600 rpm for 4 h at 75°C to obtain a modified slurry; filter and wash the modified slurry, and dry it at 100°C for 8 h to obtain 115 parts of aluminum sol modified titanium dioxide;

[0043] S2. 115 parts of aluminum sol-modified titanium dioxide, 50 parts of mica iron oxide, 50 parts of barium sulfate and 5.5 parts of nano-cerium oxide were added to a mixed solvent consisting of 24 parts of xylene and 6 parts of propylene glycol methyl ether acetate. The mixture was dispersed at 1200 rpm for 60 min at 35 °C to obtain a mixed slurry. Subsequently, 90 parts of epoxy resin and 3.25 parts of 2-aminobenzimidazole were added, and the mixture was stirred at 750 rpm for 2.5 h at 55 °C to obtain a coating base material.

[0044] S3. Add 24 parts xylene, 6 parts propylene glycol methyl ether acetate, 31.875 parts polyamide curing agent, and 10.625 parts modified alicyclic amine curing agent to the coating base material, and stir at 500 rpm for 40 min at 30°C to obtain the industrial coating.

[0045] Comparative Example 2: The purpose of this comparative example is to verify the effect of epoxy silane-modified titanium dioxide on the performance of industrial coatings after replacing aluminum sol-epoxy silane synergistic modification of titanium dioxide.

[0046] S1. Mix 75 parts of ethanol and 95 parts of deionized water and stir at 450 rpm for 60 min at 35 °C; then add 100 parts of titanium dioxide and stir at 750 rpm for 2 h at 40 °C; then add 11.5 parts of γ-glycidyl etheroxypropyltrimethoxysilane and stir at 600 rpm for 4 h at 75 °C to obtain a modified slurry; filter and wash the modified slurry and dry it at 100 °C for 8 h to obtain 115 parts of epoxysilane modified titanium dioxide.

[0047] S2. 115 parts of epoxy silane-modified titanium dioxide, 50 parts of mica iron oxide, 50 parts of barium sulfate and 5.5 parts of nano-cerium oxide were added to a mixed solvent consisting of 24 parts of xylene and 6 parts of propylene glycol methyl ether acetate. The mixture was dispersed at 1200 rpm for 60 min at 35 °C to obtain a mixed slurry. Subsequently, 90 parts of epoxy resin and 3.25 parts of 2-aminobenzimidazole were added, and the mixture was stirred at 750 rpm for 2.5 h at 55 °C to obtain a coating base material.

[0048] S3. Add 24 parts xylene, 6 parts propylene glycol methyl ether acetate, 31.875 parts polyamide curing agent, and 10.625 parts modified alicyclic amine curing agent to the coating base material, and stir at 500 rpm for 40 min at 30°C to obtain the industrial coating.

[0049] Comparative Example 3: The purpose of this comparative example is to verify the effect of not adding 2-aminobenzimidazole on the performance of industrial coatings.

[0050] S1. 15 parts of aluminum sol were added to a mixed solvent consisting of 75 parts of ethanol and 95 parts of deionized water, and stirred at 450 rpm for 60 min at 35 °C to obtain an aluminum sol dispersion. Then, 100 parts of titanium dioxide were added to the aluminum sol dispersion, and stirred at 750 rpm for 2 h at 40 °C. Then, 11.5 parts of γ-glycidyl etheroxypropyltrimethoxysilane were added, and stirred at 600 rpm for 4 h at 75 °C to obtain a modified slurry. The modified slurry was filtered, washed, and dried at 100 °C for 8 h to obtain 115 parts of aluminum sol-epoxysilane synergistic modified titanium dioxide.

[0051] S2. 115 parts of aluminum sol-epoxy silane synergistic modified titanium dioxide, 50 parts of mica iron oxide, 50 parts of barium sulfate and 5.5 parts of nano-cerium oxide were added to a mixed solvent consisting of 24 parts of xylene and 6 parts of propylene glycol methyl ether acetate, and dispersed at 1200 rpm for 60 min at 35°C to obtain a mixed slurry; then 90 parts of epoxy resin were added, and the mixture was stirred at 750 rpm for 2.5 h at 55°C to obtain the coating base material.

[0052] S3. Add 24 parts xylene, 6 parts propylene glycol methyl ether acetate, 31.875 parts polyamide curing agent, and 10.625 parts modified alicyclic amine curing agent to the coating base material, and stir at 500 rpm for 40 min at 30°C to obtain the industrial coating.

[0053] Performance testing:

[0054] 1. Salt spray resistance test

[0055] The coatings prepared in the examples and comparative examples were uniformly applied to the surface of sandblasted Q235 steel plates, with the dry film thickness controlled at (80±5) μm. After curing at 25℃ for 7 days, the coatings were ready for use. The neutral salt spray test was conducted, placing the samples in a salt spray chamber using a 5% sodium chloride solution as the corrosive medium. The test temperature was maintained at 35℃, and continuous spraying continued until obvious rust, blistering, or peeling appeared on the coating surface. The salt spray resistance time was recorded and expressed in hours.

[0056] 2. Artificially accelerated weathering performance test

[0057] The coatings prepared in the examples and comparative examples were uniformly applied to the surface of tinplate, with a dry film thickness controlled at (80±5) μm. After curing at 25℃ for 7 days, the coatings were ready for use. Artificial accelerated weathering tests were conducted using a UV aging test chamber. The UV wavelength was set to 340 nm, the irradiation intensity to 0.89 W / m², and the cycling conditions were 8 hours of UV irradiation at 60℃ and 4 hours of condensation at 50℃. During the test, the surface chalking, cracking, and gloss loss of the coating were observed periodically. The test was terminated when significant coating failure was observed, and the weathering time was recorded in hours (h).

[0058] 3. Adhesion test

[0059] The coatings prepared in the examples and comparative examples were uniformly applied to the surface of Q235 steel plates, and the dry film thickness was controlled at (80±5) μm. The coatings were cured at 25℃ for 7 days before use. The adhesion of the coatings was tested using a cross-cut test. One hundred squares were cut into the coating surface in both the longitudinal and transverse directions. Standard adhesive tape was applied and then quickly peeled off. The adhesion grade was assessed based on the degree of coating peeling; a lower grade indicated better adhesion.

[0060] 4. Electrochemical impedance spectroscopy test

[0061] The coatings prepared in the examples and comparative examples were uniformly coated onto the surface of Q235 steel plates, with the dry film thickness controlled at (80±5) μm. After curing at 25℃ for 7 days, the coatings were ready for use. Electrochemical workstations were used for testing, with the coated sample as the working electrode, a platinum sheet as the counter electrode, and a saturated calomel electrode as the reference electrode. Electrochemical impedance spectroscopy was performed in a 3.5% sodium chloride solution, with a test frequency range of 10 Hz. -2~10 5 The impedance modulus at 0.01 Hz characterizes the shielding performance of the coating. The larger the impedance modulus, the better the anti-corrosion performance of the coating.

[0062] Table 1. Performance test results of the examples and comparative examples.

[0063] Example 1 1450 1750 1 <![CDATA[2.15×10 9 ]]> Example 2 1980 2350 0 <![CDATA[7.36×10 9 ]]> Example 3 1820 2150 0 <![CDATA[5.88×10 9 ]]> Comparative Example 1 1220 1500 2 <![CDATA[1.21×10 9 ]]> Comparative Example 2 1150 1420 3 <![CDATA[9.54×10 8 ]]> Comparative Example 3 980 1230 2 <![CDATA[6.82×10 8 ]]>

[0064] According to Table 1, the low-VOC environmentally friendly titanium-silicon synergistic modified industrial coatings prepared in Examples 1-3 are significantly better than those in Comparative Examples 1-3 in terms of performance indicators such as salt spray resistance time, weather resistance time, adhesion grade, and electrochemical impedance modulus. This indicates that the synergistic effect of aluminum sol-epoxy silane synergistic modification of titanium dioxide and 2-aminobenzimidazole can effectively improve the comprehensive protective performance of industrial coatings.

[0065] The salt spray resistance test results show that Example 2 achieved a salt spray resistance time of 1980 hours, significantly higher than Examples 1 and 3, and also far exceeding Comparative Examples 1-3. This indicates that the synergistic modification of aluminum sol and epoxy silane can significantly improve the interfacial bonding ability between titanium dioxide and epoxy resin, resulting in a denser and more stable protective structure. Comparative Examples 1 and 2, using single modification methods, showed lower salt spray resistance than Example 2, indicating that single modification is insufficient to simultaneously enhance both the inorganic protective layer and the interfacial coupling layer, while synergistic modification produces a more significant anti-corrosion enhancement effect.

[0066] The results of the accelerated weathering performance test show that Example 2 achieved a weathering time of 2350 hours, significantly better than the other examples and all comparative examples. Analysis suggests that the inorganic alumina network layer formed by the alumina sol improves the surface stability of the titanium dioxide, while the epoxy silane enhances the interfacial bonding between the pigment and the resin. Together, these factors reduce the destructive effects of ultraviolet light and humid environments on the coating structure. Simultaneously, the nano-cerium oxide provides some shielding against ultraviolet light, further enhancing the coating's weather resistance.

[0067] The adhesion test results show that the adhesion grades of Examples 2 and 3 both reached level 0, while Example 1 reached level 1. Comparative Examples 1-3 all showed varying degrees of decrease. Specifically, Comparative Example 3, which removed 2-aminobenzimidazole while maintaining the synergistic modification system, exhibited a significant decrease in adhesion. This indicates that 2-aminobenzimidazole can enhance the interfacial forces within the coating, improve the bonding effect between the resin system and the modified titanium dioxide, thereby increasing the coating's adhesion to the substrate.

[0068] The electrochemical impedance spectroscopy results show that Example 2 achieved an impedance modulus of 7.36 × 10⁻⁶ at 0.01 Hz. 9 Ω·cm2 The impedance modulus was significantly higher than that of all comparative examples. The higher impedance modulus indicates that the coating can effectively prevent corrosive media from penetrating into the metal substrate. In particular, the impedance modulus of comparative example 3 decreased the most significantly, indicating that 2-aminobenzimidazole can not only enhance the structural stability of the coating, but also form a more complete barrier network with synergistically modified titanium dioxide, thereby improving the electrochemical protection capability of the coating.

[0069] In summary, this invention, by constructing an aluminum sol-epoxy silane synergistic modification system for titanium dioxide and introducing 2-aminobenzimidazole as a functional synergist, achieves a synergistic enhancement effect of the inorganic protective layer, the interfacial coupling layer, and the organic synergist system, thereby significantly improving the salt spray resistance, weather resistance, adhesion, and electrochemical protective performance of industrial coatings. Example 2, using the median ratio and suitable process conditions, exhibits the best overall performance, fully demonstrating the excellent application value and promising prospects of this invention.

Claims

1. A low-VOC, environmentally friendly titanium-silicon synergistic modified industrial coating, characterized in that, The raw materials include the following parts by weight: 80-150 parts of aluminum sol-epoxy silane synergistic modified titanium dioxide; 60-120 parts of epoxy resin; 0.5-6 parts of 2-aminobenzimidazole; 20-80 parts of mica iron oxide; 20-80 parts of barium sulfate; 1-10 parts of nano cerium oxide; 25-60 parts of curing agent; and 40-120 parts of organic solvent. The aluminum sol-epoxy silane synergistic modified titanium dioxide is prepared by surface synergistic coating modification of titanium dioxide with aluminum sol and γ-glycidyl etheroxypropyltrimethoxysilane.

2. The low-VOC environmentally friendly titanium-silicon synergistic modified industrial coating according to claim 1, characterized in that, The aluminum sol-epoxysilane synergistic modified titanium dioxide comprises the following raw materials in parts by weight: 100 parts titanium dioxide; 5-25 parts aluminum sol; 3-20 parts γ-glycidyl etheroxypropyltrimethoxysilane; 30-120 parts ethanol; and 40-150 parts deionized water.

3. A low-VOC environmentally friendly titanium-silicon synergistic modified industrial coating according to claim 1 or 2, characterized in that, The preparation method of the aluminum sol-epoxy silane synergistic modified titanium dioxide includes the following steps: (1) Add aluminum sol to a mixed solvent consisting of ethanol and deionized water, stir and mix evenly to obtain an aluminum sol dispersion; (2) Add titanium dioxide to the aluminum sol dispersion for dispersion treatment, and then add γ-glycidyl etheroxypropyltrimethoxysilane for surface modification reaction to obtain modified slurry; (3) The modified slurry is filtered, washed and dried to obtain aluminum sol-epoxy silane synergistic modified titanium dioxide.

4. The low-VOC environmentally friendly titanium-silicon synergistic modified industrial coating according to claim 3, characterized in that, The reaction conditions for step (1) are: stirring at 300-600 rpm for 30-90 min at 25-45℃.

5. The low-VOC environmentally friendly titanium-silicon synergistic modified industrial coating according to claim 3, characterized in that, In step (2), the reaction conditions for dispersing titanium dioxide are: at 25-50°C, stirring at 500-1000 rpm for 1-3 hours; the reaction conditions for surface modification are: at 60-85°C, stirring at 400-800 rpm for 2-6 hours.

6. The low-VOC environmentally friendly titanium-silicon synergistic modified industrial coating according to claim 3, characterized in that, The reaction conditions for step (3) are: after filtration, drying at 80-120℃ for 6-12 hours.

7. The low-VOC environmentally friendly titanium-silicon synergistic modified industrial coating according to claim 1, characterized in that, The curing agent is a mixture of polyamide curing agent and modified alicyclic amine curing agent in a mass ratio of 3 to 4:1; the organic solvent is a mixture of xylene and propylene glycol methyl ether acetate in a mass ratio of 4 to 6:

1.

8. A method for preparing a low-VOC, environmentally friendly titanium-silicon synergistic modified industrial coating, characterized in that, The preparation method includes the following steps: S1, aluminum sol-epoxy silane synergistic modification of titanium dioxide, mica iron oxide, barium sulfate and nano cerium oxide are added to a portion of organic solvent for pre-dispersion to obtain a mixed slurry; S2, add epoxy resin and 2-aminobenzimidazole to the mixed slurry, and continue to disperse and mix evenly to obtain the coating base material; S3, add the remaining organic solvent and curing agent to the coating base material, mix evenly to obtain a high weather-resistant titanium-based anti-corrosion coating composition.

9. The method for preparing a low-VOC environmentally friendly titanium-silicon synergistic modified industrial coating according to claim 8, characterized in that, The reaction conditions for step S1 are: dispersion at 800–1500 rpm for 30–90 min at 25–45 °C.

10. The method for preparing a low-VOC environmentally friendly titanium-silicon synergistic modified industrial coating according to claim 8, characterized in that, The reaction conditions for step S2 are: stirring at 500-1000 rpm for 1-4 hours at 40-70°C; the reaction conditions for step S3 are: stirring at 300-800 rpm for 20-60 minutes at 20-40°C.